(untitled) (MATEMATIKA, 2004)
Berbagai penganggar konsistent telah dicadangkan untuk parameter kecerunan bagi hubungan fungsian linear tanpa replika. Artikel ini memberikan perbandingan berangka bagi penganggar-penganggar tersebut. Adalah diharapkan kita dapat mencadangkan pemilihan yang sesuai baginya. Katakunci: Penganggar konsistent; parameter kecerunan; hubungan fungsian linear tanpa replika. A variety of consistent estimators of the slope parameter for unreplicated linear functional relationship model have been proposed over the years. This paper gives some numerical comparisons among them. As a result we are able to make specific recommendations regarding a choice among them. Keywords: Consistent estimator; slope parameter; unreplicated linear functional relationship model.